Development of Logistics Services in Kazakhstan and Evaluation of the Opinions of Logistics Company Managers with the Nvivo Program - Kelesbayev, D.N.; Bolganbayev, D.N.; Myrzabekkyzy, K.; Sultankhanova, G.T. (BUKETOV BUSINESS REVIEW, 2022)
Object: This study aims to review the transportation sector in Kazakhstan; evaluate the current status and performance of logistics centers; and identify the main problems and root causes. Our research problem is to determine whether it is possible to establish a logistics center sufficient to meet the expectations of both the country and the logistics companies and, if possible, to determine the requirements of that center. Methods: Interviews, NVivo package program, observation, document analysis, coding techniques. Results: The qualitative analysis revealed the expectations of the sector representatives from a logistics center and the requirements that a center should meet to support the development of the sector and the country’s economy. The fact that concepts such as logistics center, logistics, and logistics service are present in almost all interviews shows the sensitivity of the sector to the subject. Conclusions: Kazakhstan can create an integrated complex that complies with international standards, can provide quality service for any goods in every direction and distance, and can provide all kinds of barrier-free transportation